The Influence of TikTok Social Media and Fear of Missing Out on Skintific Purchase Intention among Urban TikTok Users in Bandung - Nugroho, Faisal Adi; Sutisna, Ma'mun (Manunggal Halim Jaya, 2026)
In the digital age, TikTok has emerged as a dominant platform influencing consumer behavior, particularly in the beauty and skincare industry. While previous research has explored the general impact of social media on purchase intention, limited studies have focused on the combined effect of TikTok-specific content and the psychological phenomenon of Fear of Missing Out (FoMO) within a localized urban context. This study aims to investigate the influence of TikTok and FoMO on the purchase intention of the skincare brand Skintific among urban TikTok users in Bandung, Indonesia. Employing a quantitative explanatory approach, data were collected from 331 respondents aged 18–34 through an online survey using non-probability purposive sampling. The data were analyzed using multiple linear regression via SPSS software. The findings reveal that both TikTok social media and FoMO have a positive and statistically significant influence on consumer purchase intention. Uniquely, this study identifies how trendy, emotionally engaging TikTok content synergizes with FoMO to create psychological urgency, leading to heightened purchase desire, especially for skincare products that promise immediate social validation. By situating the analysis within the context of a rapidly growing Southeast Asian urban market, this research provides nuanced insights into how digital content and emotional triggers jointly shape e-commerce behavior. The study offers practical implications for marketers, suggesting that effective TikTok strategies should combine compelling content with psychological cues to maximize consumer engagement. This research contributes to the evolving digital marketing and behavioral psychology literature by highlighting a context-specific, dual-factor influence on consumer decision-making.